THE POLITICAL OF LAW TO THE GOVERNMENT POLICY ABOUT REMISSION - Yudistira, Erik; Marsaid, Marsaid; Rochmiyatun, Siti (Nurani, 2021)
The law refers to a rule of life in accordance with the ideals of living together and the principles of justice. The content of the rule of law should be fair. Without justice, law is only formalized violence. The law is felt to be important when dealing with injustice. Through a political perspective, law is viewed as a product or output of a political process or the result of consideration and formulation of public policy. However, besides law as a product of political consideration, there is political law which is the basis or basis of policy for determining the laws that should apply in the state. As mandated by the Constitution, one of which produces a remission regulation, Remission is essentially the right of all prisoners and applies to anyone as long as the prisoner is serving a life sentence. The problem that arises is that the application of remission requirements is not in accordance with the expected objectives. Thus, the purpose of this study is to determine the implementation of remittances in Government Regulation Number 99 of 2012 concerning Terms and Procedures for the Implementation of the Rights of the Convicted; and analysis of Political Law and Government Policy on Remissions in Government Regulation Number 99 of 2012 concerning Remissions in Article 34A seen from Article 34. This type of research is qualitative using secondary data. The research results are if we look at the corners of the hierarchy of the laws and regulations stipulated in Article 7 of Law Number 12 of 2011 concerning the Establishment of Legislative Regulations, then the provisions for granting the remission of corruptors in Government Regulation Number 99 of 2012 are contrary to Article 5 of the Law on Corrections. This is because the substance contained in Article 34 Paragraph (1) a and b of this Government Regulation is a new norm that is contrary to the philosophy, objectives, vision and mission of the Law on Corrections itself which prohibits discriminatory treatment and treatment of prisoners.